2013
DOI: 10.1161/circinterventions.113.000463
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Repair of Type B Aortic Dissection

Abstract: Background-Thoracic endovascular aortic repair (TEVAR) represents a therapeutic concept for type B aortic dissection.Long-term outcomes and morphology after TEVAR for uncomplicated dissection are unknown. Methods and Results-A total of 140 patients with stable type B aortic dissection previously randomized to optimal medical treatment and TEVAR (n=72) versus optimal medical treatment alone (n=68) were analyzed retrospectively for aortaspecific, all-cause outcomes, and disease progression using landmark statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
88
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 923 publications
(92 citation statements)
references
References 43 publications
3
88
0
1
Order By: Relevance
“…1,9,19,21 As a result, it is likely that the acuity of presentation of type B dissections undergoing repair was “diluted” over time by selection of patients for repair who presented with uncomplicated subacute or chronic disease. This effect has probably also contributed to improvements in perioperative mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,9,19,21 As a result, it is likely that the acuity of presentation of type B dissections undergoing repair was “diluted” over time by selection of patients for repair who presented with uncomplicated subacute or chronic disease. This effect has probably also contributed to improvements in perioperative mortality.…”
Section: Discussionmentioning
confidence: 99%
“…During the study period, TEVAR emerged as a potential therapy to prevent aneurysmal degeneration of chronic dissection. 8,9 Although the validity of this is still being studied, the practice of treating chronic dissection with TEVAR has presumably been adopted by some, and it is unclear how this has affected national practice patterns. Similarly, it is unknown if there have been any changes in dissection anatomy or timing of intervention in patients undergoing open repair, factors that may have contributed to improved perioperative mortality in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Favorable aortic remodeling and a reduction in emergent crossover TEVARs were also observed in those randomized to early TEVAR (57). The results of the initial INSTEAD trial demonstrated that survival after Type B dissection improved with stringent blood pressure control and close surveillance.…”
Section: Future Directionsmentioning
confidence: 96%
“…This entails intensive anti-impulse therapy; the cornerstone of which is reduction of pressure on the aortic wall and subsequent decreased propagation of the false lumen. While a majority of patients so treated are discharged with no complications; the long-term outcomes are perturbing with high mortality and complication rates [7]. Subsequently, questions abound about the possibility of multimodal therapy with adjunctive TEVAR in a bid to improve the outcomes [5].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, questions abound about the possibility of multimodal therapy with adjunctive TEVAR in a bid to improve the outcomes [5]. This stent–graft placement occludes the primary intimal tear promoting false lumen thrombosis and subsequent aortic remodeling [3]; with resultant reduction of disease progression, late adverse events and aorta specific mortality [7, 8]. Despite this, however, the use of TEVAR in uncomplicated AAD-B remains controversial; and is not without risks, one of which is PIS.…”
Section: Discussionmentioning
confidence: 99%